2019
DOI: 10.3389/fevo.2019.00178
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplasma Infection Influences Gene Expression in American Cranberry

Abstract: Cranberry false blossom disease (CFBD) is caused by a leafhopper-vectored phytoplasma infection. CFBD results in distinctive branching of the upright shoots (witches' broom) and the formation of deformed flowers that fail to produce fruit. This disease is reemerging and poses a serious threat to the cranberry industry. To determine the impact of the disease on host gene expression, we compared transcriptome profiles between plants with CFBD and uninfected cranberry plants. We found that phytoplasma infection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 92 publications
(126 reference statements)
2
8
1
Order By: Relevance
“…Previous studies examining the effects of phytoplasma infection on phytohormones have produced mixed results ( Dermastia, 2019 ), with some showing activation of the SA pathway ( Ahmad et al, 2013 ; Prezelj et al, 2016 ), while others have shown activation of the JA pathway ( Musetti et al, 2013 ; Luge et al, 2014 ; Paolacci et al, 2017 ). Contrary to this study, however, previous studies in cranberries found no effect of phytoplasma infection on SA concentrations ( Pradit et al, 2020 ) or on the expression of SA-related genes ( Pradit et al, 2019b ). Although the mechanisms underlying the variable effects of infection observed across study systems remain unclear, it is known that phytohormone levels can change based on plant age and growing conditions ( Paolacci et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Previous studies examining the effects of phytoplasma infection on phytohormones have produced mixed results ( Dermastia, 2019 ), with some showing activation of the SA pathway ( Ahmad et al, 2013 ; Prezelj et al, 2016 ), while others have shown activation of the JA pathway ( Musetti et al, 2013 ; Luge et al, 2014 ; Paolacci et al, 2017 ). Contrary to this study, however, previous studies in cranberries found no effect of phytoplasma infection on SA concentrations ( Pradit et al, 2020 ) or on the expression of SA-related genes ( Pradit et al, 2019b ). Although the mechanisms underlying the variable effects of infection observed across study systems remain unclear, it is known that phytohormone levels can change based on plant age and growing conditions ( Paolacci et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
“…The target gene (“UnkPhyto”) was selected based on previous transcriptome data and RT-qPCR data showing that this gene is stable and expressed only in cranberry leaves infected by phytoplasma ( Pradit et al, 2019b ). The primer used for the target gene is listed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations